The Influence of Fintech nn The Efficinecy and Stability of The Sharia Financial System - Vidiati, Cory; Cucu Putria, Andieni (Journal of Islamic Economic Development, 2023)
The influence of Financial Technology (Fintech) on the efficiency and stability of the Islamic financial system has become the center of attention in modern financial literature. This research uses a literature study method to investigate the impact of Fintech in the context of Islamic finance. The main findings show that Fintech adoption has positively contributed to operational efficiency, reduced administrative costs, and increased accessibility of Islamic financial services. However, the regulatory challenges faced in balancing technological innovation and Sharia principles are a major highlight. In addition, the literature describes risks related to technological changes that can affect the stability of the Islamic financial system. This research provides recommendations for increasing cooperation between Islamic financial institutions and Fintech start-ups, developing responsive regulations, and expanding empirical research to test the impact of Fintech directly. In conclusion, this research provides in-depth insights into the evolution of Islamic finance in the Fintech era, providing a basis for better understanding and developing relevant policies.